Evaluation of transmit efficiency and SAR for a tight fit transceiver human head phased array at 9.4 T. (28th December 2016) - Avdievich, N.I.; Hoffmann, J.; Shajan, G.; Pfrommer, A.; Giapitzakis, I.A.; Scheffler, K.; Henning, A.
Abstract : Ultra‐high field (UHF, ≥7 T) tight fit transceiver phased arrays improve transmit (Tx) efficiency ( B 1 + /√ P ) in comparison with Tx‐only arrays, which are usually larger to fit receive (Rx)‐only arrays inside. One of the major problems limiting applications of tight fit arrays at UHFs is the anticipated increase of local tissue heating, which is commonly evaluated by the local specific absorption rate (SAR). To investigate the tradeoff between Tx efficiency and SAR when a tight fit UHF human head transceiver phased array is used instead of a Tx‐only/Rx‐only RF system, a single‐row eight‐element prototype of a 400 MHz transceiver head phased array was constructed. The Tx efficiency and SAR of the array were evaluated and compared with that of a larger Tx‐only array, which could also be used in combination with an 18‐channel Rx‐only array. Data were acquired on the Siemens Magnetom whole body 9.4 T human MRI system. Depending on the head size, positioning and the RF shim strategy, the smaller array provides from 11 to 23% higher Tx efficiency. In general, the Tx performance, evaluated as B 1 + /√SAR, i.e. the safety excitation efficiency (SEE), is also not compromised. The two arrays provide very similar SEEs evaluated over 1000 random RF shim sets. We demonstrated that, in general, the tight fit transceiver array improves Tx performance without compromising SEE. However, in specific cases, the SEE value may vary, favoring one of the arrays, and therefore must be carefully evaluated. Abstract : To investigate the tradeoff between transmit (Tx) efficiency ( B 1 + /√P) and specific absorption rate (SAR) when a tight fit ultra‐high field human head transceiver (TxRx) phased array is used instead of a larger Tx‐only array, an eight‐element 400 MHz head TxRx‐array was constructed. The Tx efficiency and SAR of the array were compared with those of a larger Tx‐only array. We demonstrated that the tight fit array improves Tx performance from 11 to 23%. In general, Tx performance, evaluated as B 1 + /√SAR, is also not compromised.